Development of Rapid and Facile Solid‐Phase Synthesis of PROTACs via a Variety of Binding Styles. Issue 7 (13th July 2022) - Xu, Hanqiao; Kurohara, Takashi; Takano, Reina; Yokoo, Hidetomo; Shibata, Norihito; Ohoka, Nobumichi; Inoue, Takao; Naito, Mikihiko; Demizu, Yosuke
Abstract: Optimizing linker design is important for ensuring efficient degradation activity of proteolysis‐targeting chimeras (PROTACs). Therefore, developing a straightforward synthetic approach that combines the protein‐of‐interest ligand (POI ligand) and the ligand for E3 ubiquitin ligase (E3 ligand) in various binding styles through a linker is essential for rapid PROTAC syntheses. Herein, a solid‐phase approach for convenient PROTAC synthesis is presented. We designed azide intermediates with different linker lengths to which the E3 ligand, pomalidomide, is attached and performed facile PROTACs synthesis by forming triazole, amide, and urea bonds from the intermediates. Abstract : A convenient solid‐phase PROTAC synthesis method that allows the conjugation of a POI ligand and an E3 ligand with linkers of various binding styles, was developed. Specifically, PROTACs with triazole, amide, and urea bonds were rapidly synthesized from azide intermediates on the resin.